Shooting Ability Of Petanque Athletes In Palopo: The Role Of Physical Conditions And Kinesthetic Perceptions - Fadly Rhamadhan; Rachmat Hidayat; Irsan Kahar; Nurwahidin Hakim (STKIP Muhammadiyah Kuningan, 2023)
Petanque is a relatively new sport in the developin g City of Palopo. However, petanque athletes need help with physical condition aspects that can be seen from the training and competition processes and kinesthetic perception. This research aims to determine the relationship between physical condition and kinesthetic perception of shooting ability. Several physical elements support the shooting in petanque: arm strength, hand-eye coordination, balance and kinesthetic perception. The research results show a significant relationship between physical condition and kinesthetic perception of shooting ability. It can be concluded that a petanque athlete's shooting ability has a strong relation with physical condition aspect and kinesthetic perception. This research is expected to examine aspects of the physical condition to contribute to the Petanque sport of Palopo City.